EKSPLORASI MIKORIZA ARBUSKULA PADA BEBERAPA KEDALAMAN TANAH DI PERAKARAN RUMPUT BANTENG PADA LAHAN PASCATAMBANG - Yhudo Tomo; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The presence of mycorrhizae can reduce the level of poisoning caused by heavy metals in post-mining land and support plant growth. Post-mining land is generally only a few types of mycorrhizae that can adapt, especially post-mining land. This research was conducted to determine the presence, types and distribution of mycorrhizae as well as the relationship between soil depth and mycorrhizal distribution and soil chemical properties at various depths in the rhizosphere of bull grass as the dominant vegetation in post-coal mining land. The results showed that there were arbuscular mycorrhizae at each soil depth with different population density levels, namely 273 spores 100 g-1 soil at a depth of 0 - 10 cm (K10); 239 spores 100 g-1 soil at a depth of 10 – 20 cm (K20) and 155 spores 100 g-1 soil at a depth of 20 – 30 cm (K30). The arbuscular mycorrhizae found at all soil depths are of the same type, which is included in the genus Glomus. Soil depth with the number of arbuscular mycorrhizal distribution (r count -0.7754> r table -0.4973) has a very strong relationship and with soil pH (r count -0.6309> r table -0.4973) has a strong relationship. The number of distribution of arbuscular mycorrhizae with soil pH (r count 0.5943> r table 0.4973) has a strong relationship